2019
DOI: 10.1021/acsami.8b20422
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite Imidazolate Framework Membranes on Polymeric Substrates Modified with Poly(vinyl alcohol) and Alginate Composite Hydrogels

Abstract: Poly­(vinyl alcohol)–sodium alginate composite hydrogels were first introduced to synthesize robust and well-intergrown zeolite imidazolate framework (ZIF)/polymer hollow fiber membranes. Through enough adsorption interaction with metal ions by chelation, sufficient nucleation sites for in situ metal–organic framework (MOF) preparation are provided. Using this method, we can not only easily prepare defect-free MOF membranes ignoring the complex modification process and seed deposition but also structurally fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…As such, research on polymeric membrane material and membrane technology maintained its focus on membrane modification to produce materials with intrinsic composite features [2,[35][36][37]. This involves a straightforward process of conjoining or blending polymeric material with hydrophilic nanoadditives such as nanoparticles, carbon nanotubes and zeolites [1,23,38,39]. Typically, zeolite materials have demonstrated the ability to enhance membranes' water flux, permeability and antifouling characteristics, as reported in several studies [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…As such, research on polymeric membrane material and membrane technology maintained its focus on membrane modification to produce materials with intrinsic composite features [2,[35][36][37]. This involves a straightforward process of conjoining or blending polymeric material with hydrophilic nanoadditives such as nanoparticles, carbon nanotubes and zeolites [1,23,38,39]. Typically, zeolite materials have demonstrated the ability to enhance membranes' water flux, permeability and antifouling characteristics, as reported in several studies [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, metal–organic framework (MOF) materials have been widely investigated, and because of their uniform pore size and high designability, they have great potential in membrane separation. Compared with mixed-matrix membranes (MMMs), substrate-supported heteroepitaxial MOF membranes have been widely studied due to their higher selectivity. However, compared to inorganic substrates, polymeric substrates with good processability and low cost have priority for industrialization. In other words, preparation of MOF membranes on polymer substrates will greatly promote the development and industrial applications of MOF membranes.…”
mentioning
confidence: 99%
“…There are several MOF membranes successfully grown on polymer substrates. However, considering the different mechanical properties between MOFs and polymers, polymer-supported MOF membranes have to be operated carefully to avoid any bending, otherwise the relatively fragile MOF membrane layers become damaged. , On the basis of this, polypropylene (PP) with a smaller Young’s modulus difference from ZIF-8 is selected as the substrate to provide flexibility, thereby reducing any possible damage of the ZIF-8 membrane layer due to bending (Figure a).…”
mentioning
confidence: 99%
“…According to these structural information, XRD patterns of bare ZIF‐9(NH 2 ) and PTA@ZIF‐9(NH 2 ) were investigated (Figure ). XRD patterns of the synthesized ZIF‐9(NH 2 ) and PTA@ZIF‐9(NH 2 ) were in good agreement with the reported XRD of ZIF‐9 . The two sharp peaks at 2θ < 10° in the XRD of bare ZIF‐9(NH 2 ), demonstrated that a highly crystalline material was obtained.…”
Section: Resultsmentioning
confidence: 99%